Perioperative sleep deprivation activates the paraventricular thalamic nucleus resulting in persistent postoperative incisional pain in mice - Li, Lei; Zhang, Huijie; Zheng, Zhenli; Ma, Nan; Zhang, Yidan; Liu, Yaping; Zhang, Jingjing; Su, Songxue; Zang, Weidong; Shao, Jinping; Cao, Jing (Frontiers in Neuroanatomy, 2022)
Background The duration of postsurgical pain is closely correlated with perioperative stress. Most patients suffer short-term sleep disorder/deprivation before and/or after surgery, which leads to extended postsurgical pain by an undetermined mechanism. The paraventricular thalamus (PVT) is a critical area that contributes to the regulation of feeding, awakening, and emotional states. However, whether the middle PVT is involved in postoperative pain or the extension of postoperative pain caused by perioperative sleep deprivation has not yet been investigated. Methods We established a model of postoperative pain by plantar incision with perioperative rapid eye movement sleep deprivation (REMSD) 6 h/day for 3 consecutive days in mice. The excitability of the CaMKIIα+ neurons in the middle PVT (mPVTCaMKIIα) was detected by immunofluorescence and fiber photometry. The activation/inhibition of mPVTCaMKIIα neurons was conducted by chemogenetics. Results REMSD prolonged the duration of postsurgical pain and increased the excitability of mPVTCaMKIIα neurons. In addition, mPVTCaMKIIα neurons showed increased excitability in response to nociceptive stimuli or painful conditions. However, REMSD did not delay postsurgical pain recovery following the ablation of CaMKIIα neurons in the mPVT. The activation of mPVTCaMKIIα neurons prolonged the duration of postsurgical pain and elicited anxiety-like behaviors. In contrast, inhibition of mPVTCaMKIIα neurons reduced the postsurgical pain after REMSD. Conclusion Our data revealed that the CaMKIIα neurons in the mPVT are involved in the extension of the postsurgical pain duration induced by REMSD, and represented a novel potential target to treat postoperative pain induced by REMSD.